Peran Pengelolaan Persediaan Barang dalam Meningkatkan Efisiensi Keuangan di CV Sumber Jaya Putra Perkara - Maria Faustina Nona; Andreas Rengga; Elisabeth Luju (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the role of inventory management in improving financial efficiency at CV. Sumber Jaya Putra Perkasa. The main problems faced by the company are manual inventory management, technological limitations, dependence on certain suppliers, and suboptimal demand planning, which affect distribution effectiveness and financial efficiency. This study uses a quantitative descriptive approach with data collection techniques through interviews, observation, and documentation. The analysis was conducted on the stock management process, inventory turnover, and its impact on storage costs and operational efficiency. The results show that good inventory management contributes significantly to increased financial efficiency. With proper stock planning, companies can minimize the risk of excess and shortage of goods, reduce storage costs (holding costs), and increase inventory turnover so that working capital can circulate more quickly. However, the inventory management system currently used by CV. Sumber Jaya Putra Perkasa still has limitations, especially in terms of digitization and information integration. This study recommends the implementation of a technology-based inventory management system, a multi-supplier strategy, and the application of demand forecasting methods to improve stock planning accuracy. With this strategy, it is hoped that the company can achieve more optimal financial efficiency and strengthen its competitiveness in the distribution industry.